Behavior of Cuscuses (Phalangeridae) - Kiroh, Hengki J. (Indonesian Cuscuses (Diprotodontia: Phalangeridae): Status and Perspective, 2022)
Indonesia with a plain area of only about 1.3% of the earth's surface is rich in various types of wildlife species and various types of ecosystems, most of which are not found in any hemisphere. In addition, Indonesia has about 27,500 plant species (10% of the world's flowering plants), 515 mammal species (12% of the world's mammals), 1,539 bird species (17% of all bird species in the world), 25% of all fish species in the world. North Sulawesi has many species of very high diversity, and approximately 70% of the 114 animal species known to exist are rare and endemic species including bear cuscus (Aillurops ursinus) (MacKinnon, 1986). The natural resources owned by the Indonesian people are the basic capital of a very strategic national development, an ecological comparative advantage that is not owned and cannot be developed by other nations and countries. Seeing the importance of nature conservation, the Indonesian government is absolutely committed to protecting 10% of the plains area and 20 million ha of coastal and marine habitats as conservation areas. Cuscus is a marsupial animal / animal (classified as marsupials). Based on several sources, the spread of cuscus is almost all over eastern Indonesia. According to animal experts, this animal is described as having a rather large and sturdy body and also having a body length the size of a two-month-old pig. The genus that includes cuscus species are Aillurops, Phalanger, Spilocuscus and Strigocuscus. Their coat coloring pattern is also distinguished into two genera, namely the genus Spilocuscus and Phalanger, each consisting of 3 to 8 species, while on the island of Sulawesi there are three endemic species of cuscus, namely Aillurops ursinus, Phalanger pelengensis and Strigocuscus celebensis.